Analisis Indeks Glikemik, Kadar Serat dan Karbohidrat Nasi dari Varietas Beras Siam (Mutiara, Unus dan Saba) - Nany Suryani; Diah Widayati; Rijanti Abdurrachim (Jurnal Kesehatan Indonesia, 2020)
Rice is the food source of carbohydrates and fiber contain enough . food stuffs with a low carbohydrate content and high fiber content tends to have a low glycemic index . consuming foods with a low glycemic index will lower blood glucose levels. In patients with diabetes mellitus .siam rice varieties of pearls , and sabaunus widely cultivated by the farmers of south kalimantan , other than that consumed by many people South Kalimantan The research objective was to determine the levels of fiber, carbohydrate and analyze differences in the glycemic index of the rice varieties of rice siam (pearl, Unus and Saba) that can be used for people with diabetes mellitus. It is an experimental research to analyze fiber, carbohydrate and glycemic index level. To determine levels of fiber used luftSchoorl method for inspection and carbohydrate levels are used the gravimetric method , while the glycemic index levels made ??by examining blood glucose levels to 8 healthy respondents . The blood glucose is examined before giving the tested food and during two hours afterwards with 30 minutes susceptible time. Results of this study found with mean fiber are 3.12%, 3.24%, and 3.07%, respectively and carbohydrate levels are 10.47%, 12,51% and 13.95%, respectively.Mean glycemic index is gained after analyzing and counting the data, 54.4% for mutiara rice, 50.1% for unus, and 53.4% for saba . Based on statistic test with repeated anova it showed that p>0.05 (0.792). From this research, it can be concluded that glycemic index level of siam rice is included in low category thus, it can be used as can alternative food for diabetic mellitus.